KIT TOOL-S2 for the Portuguese Healthcare Professional: A Psychometric Analysis - Catarina Amaral; Carlos Sequeira; Núria Albacar-Riobóo; Lara Guedes Pinho; Carme Ferré-Grau (Karger Publishers, 2024)
Introduction: Literacy of health professionals on patient safety aims to prevent and reduce risks and adverse events in healthcare. Objective: The objective of this study was to translate, adapt, and validate for Portugal of the World Health Organization Questionnaire to Assess the Implementation of the Multiprofessional Guide. Methodology: Following the cultural adaptation process, we carried out a psychometric analysis on a sample of 300 health professionals. The scale was tested for apparent and content validity. Psychometric properties were assessed using Cronbach's alpha coefficient (α) through exploratory and confirmatory factor analysis, convergent validity, and discriminant validity. Results: Exploratory factor analysis led to a tetra factor structure that accounted for 43.0% of the variance and had an overall alpha of 0.759. The hypothesized structure was submitted to confirmatory factor analysis, and the following items were eliminated from factors 1, 2, and 3 and the respective items: 7; 5; and 3, 4, 5, and 6, due to multicollinearity problems. Overall good-of-fit indexes are reliable. Conclusions: The "KIT TOOL-S2 TEXT" scale presents a factor structure with satisfactory validity and reliability results, adequately representing the constructs in question.